Nuclear Energy Production in the South China Sea basin as an International Issue(Penghasilan Tenaga Nuklear di Laut China Selatan Sebagai Isu Antarabangsa) - Mohamed, C.A.R (Universiti Kebangsaan Malaysia, 2011)
The South China Sea is divided into two parts; the northern South China Sea (nSCS) and the southern South China Sea (sSCS), where the nSCS includes Taiwan, Hong Kong and the Republic of China. The sSCS region consists of Malaysia, Thailand, Singapore, Brunei, Indonesia, Cambodia, Vietnam and the Philippines. The South China Sea is a semi-closed system and is largely influenced by the western Pacific region especially during monsoon seasons. By late 2020 countries such as Thailand, Malaysia and Indonesia intend to operate nuclear reactors as an alternative energy source. Some radionuclide produced during their operation will enter the marine ecosystem through the water cooling process. This will affect most neighboring coastal waters as trans-boundary pollution. A recent investigation on seafood conducted before the Fukushima, Japan tsunami event by The Hong Kong Observatory clearly shows that artificial radionuclides such as plutonium-239, tritium, strontium-90, carbon-14, iodine-131, cesium-137 and potassium-40 were found at positive concentration levels. There were no significant differences in Cs-137 activities both in surface and bottom water samples at the 95% confidence level. The activity of Cs-137 was found to be in the range of 1.47 to 3.36 Bq/m3 and 1.69 to 3.32 Bq/m3 for both Sabah and Sarawak, respectively.